Characterization of the Full-Length Genome Sequences and Phylogenetic Analysis of HDV Strains Isolated from Patients with Chronic HBV and HDV Infection in Kyrgyz Republic - Yu. Ostankova V.; K. Nogoybaeva A.; E. Zueva B.; K. Kasymbekova T.; S. Tobokalova T.; A. Semenov V.; Ю. Останкова В.; К. Ногойбаева А.; Е. Зуева Б.; К. Касымбекова Т.; С. Тобокалова Т.; А. Семенов В. (Izvestiya of Altai State University Journal, 2020)
Objective. The purpose of our work was molecular genetic characterization of the hepatitis D virus isolates, circulating in the region with high prevalence of HBV + HDV super-infection. Materials and methods. The study material was 64 blood serum samples obtained from Kyrgyz Republic residents - patients with chronic viral hepatitis B+D. The hepatitis D virus complete genomes were sequenced, followed by phylogenetic analysis. Results and discussion. Based on the phylogenetic analysis of 64 HDV samples, it was shown that HDV genotype 1 (96.9 %) predominates in the examined group compared with HDV genotype 2 (3.1 %). Sequences were submitted to GenBank under access No MN984407 through MN984470. When assessing the genetic variability over the examined HDV genotype 1 samples, the maximum genetic distance was 12,49 %, and the minimum – 7,41 %. Within individual clusters, the genetic distance averaged from 2.6 % to 8.5 %. Among the sequences in GenBank, the closest resemblance to the HDV-2 Kyr41 and Kyr43 samples (nucleotide identity was 92.31 % and 89.57 %, respectively) was shown for the virus described earlier in Yakutia (AJ309880). To study the genetic relationships between the analyzed HDV genotype 1 strains in comparison with the HDV reference sequences, the predicted amino acid sequence was studied (111–214). Although hepatitis B preventive measures, including vaccination, have reduced the hepatitis D incidence, there is no effective way to prevent HDV infection in HBV carriers in endemic areas. The HDV sequence molecular-genetic characterization in this study, as well as the viral genomic sequence phylogenetic analysis, will help identify pathogen transmission pathways to control and / or prevent the spread of infection. Цель работы – изучение молекулярно-генетической структуры изолятов вируса гепатита D, циркулирующих в регионе с высокой распространенностью суперинфекции вирусного гепатита (ВГ) В+ВГD. Материалы и методы. Материалом исследования послужили 64 образца сыворотки крови, полученные от жителей Кыргызской Республики, больных хроническим вирусным гепатитом В+D. Проводили секвенирование полных геномов вируса гепатита D с последующим филогенетическим анализом. Результаты и обсуждение. На основании филогенетического анализа нуклеотидных последовательностей 64 образцов ВГD показано, что в обследованной группе преобладает вирус генотипа 1 (96,9 %), по сравнению с генотипом 2 (3,1 %). Полученные нуклеотидные последовательности полных геномов изолятов вируса гепатита Дельта депонированы в международную базу данных GenBank под номерами MN984407–MN984470. При оценке дивергенции исследуемых образцов генотипа 1 максимальное генетическое расстояние составило 12,49 %, а минимальное – 7,41 %, при этом, в пределах отдельных кластеров генетическое расстояние составляло от 2,6 до 8,5 %. Среди последовательностей, представленных в базе данных GenBank, наибольшее сходство с обнаруженными нами образцами ВГD-2 Kyr41 и Kyr43 (нуклеотидная идентичность 92,31 и 89,57 % соответственно) показано для вируса, описанного ранее в Якутии (AJ309880). Для исследования генетических взаимоотношений между анализируемыми вирусными штаммами генотипа 1 изучили предсказанную аминокислотную последовательность (111–214). Хотя профилактические меры против гепатита B, включая вакцинацию, привели к снижению распространенности гепатита D, не существует эффективного способа предотвращения этой инфекции у носителей ВГВ в эндемичных районах. Молекулярно-генетическая характеристика и филогенетический анализ последовательностей ВГD, представленные в настоящем исследовании, будут способствовать идентификации путей передачи патогена для контроля и/или предотвращения распространения инфекции.